Styles of Coping with Stress among Girls from the Group of Anorexia Risk - Jaros, Katarzyna; Oszwa, Urszula (INSTED: Interdisciplinary Studies in Education & Society, 2014)
The purpose of the study was to find differences in styles of coping with stress in the group of teenage girls (N = 189) with the risk of anorexia (n = 23) and in the control group (n = 23). The relation between styles of coping with stress and the tendency to respond with abnormal attitudes towards eating and perception of the body in difficult situations in both groups was analyzed as well. There was KSJ used to assess the risk of anorexia and CISS to assess styles of coping with stress. The subjects with the risk of anorexia indicated significant preference of emotional style of coping with stress (t = 4,56, p < 0,01) and the control group used the task style more often (t = ?2,68, p < 0,05). There was a significant moderate correlation between styles of coping with stress and tendency to respond with abnormal attitude towards eating and perception of the body in difficult situations in both groups. High tendency in the group with the anorexia risk correlated with the preference of emotional style (rho = 0,45; p < 0,05) and avoidance style (rho = 0,42; p<0,05) of coping with stress. Low tendency in control subjects correlated with the preference of task style of coping with stress (rho = 0,46; p < 0,05). Predisposition to use ineffective and maladaptive styles of coping with stress (avoidance and emotional styles) plays a role in the mechanism of anorexia and preference of active and efficient ways of coping with stress (task style) could be one of the factors protecting teenagers against this disorder.